Strategi Penghimpunan Dana Zakat Pada Organisasi Pengelola Zakat Di Kabupaten Bantul - Wikaningtyas, Suci Utami; Sulastiningsih, Sulastiningsih (JURNAL RISET MANAJEMEN SEKOLAH TINGGI ILMU EKONOMI WIDYA WIWAHA PROGRAM MAGISTER MANAJEMEN, 2015)
The level of poverty in Bantul regency is higher than the average of poverty in Yogyakart province. One of the way to decrease poverty is zakat. Decreasing of poverty can be efficient and effective, if zakat collection and distribution by zakat institution. In fact, zakat collection in zakat institution in Bantul regency is increase, but it is lower than zakat potentially. It is 10 pecent only. Furthermore, zakat institutions in Bantul regency need efficient and effective zakat collection strategy. Based on the information, this research use tool of analysis is Matriks SWOT 8K. The steps of this analysis such as determining variable of streghts, weaknesses, opportinities and threaths, determining indicator, determining value of equality, determining position of zakat instititution, finally determining strategy of zakat collection. The result of this research is the position of akat institions in Bantul regency is IB Quadrant and IIA Quadrant. So, Zakat Institutions should implement aggressive maintance strategy and stable growth strategy.Key Word : poverty, zakat, strategy